PELAYANAN PENINGKATAN KEMAMPUAN MELAKSANAKAN PENELITIAN DAN PENGEMBANGAN PADA GURU PAUD DI KABUPATEN LOMBOK BARAT - Era Sativa, Filsa; Karta, I Wayan; Astini, Baik Nilawati; Jaelani, Abdul Kadir (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2023)
Teachers play a vital role in the field of education, and having standard competencies related to their duties and responsibilities is essential. However, there is still a need for teachers to enhance their skills in supporting the learning process. Given this, the initiative to conduct service improvement activities focused on research and development for Early Childhood Education (PAUD) Teachers in West Lombok District is highly relevant. The implementation of these activities is divided into three stages: concept introduction stage, practical stage for preparing research and development proposals, and follow-up program preparation stage. This program commenced in early June and extended until September 2023, and it engaged a team of four implementation officers, two students, and 18 PAUD teachers in West Lombok District. Each phase of the program included assessments and evaluations to measure the level of competency achieved. Data were collected through tests and observations, along with the analysis of work products. The results of the service initiative showed that the mastery of research and development concepts and the preparation of draft research and development proposals after the service were included in the good category with an average score for understanding the concept of 74.56% and for preparing research and development proposals an average of 76.7% The results of this service initiative indicated significant progress. After attending the workshop, there was a noticeable improvement in the understanding of research and development concepts among PAUD teachers. Initially, their understanding was rated as